Media Komunikasi Berbasis Web Online Dalam Kegiatan Pembelajaran Jarak Jauh Universitas Duta Bangsa Surakarta - Yuliana, Margaretha Evi; Alifi, Muhammad Redito; Hidayah, Erika Nur (TIN: Terapan Informatika Nusantara, 2021)
E-Learning is a media to using internet technology be used in developing knowledge, abiliti, and skills through internet technology-based media. Delivering of learning materials via internet media to students using e-learning. The use of e-learning makes it easier to manage and useful learning content is an elaboration of the Learning Management System. The target of holding the research is to describe learning, analyze the effectiveness of learning, and obtain information about the obstacles faced during this learning, in order to increase the participation of online media in order to support the best learning for students of Universitas Duta Bangsa Surakarta. The research method used is quantitative research methods. Where the data collection technique used is a survey by distributing questionnaires and then filled in by students. Based on the results of research conducted by involving 57 respondents, data on the level of web accessibility can be obtained online. 14% of respondents said it was difficult, 62% said moderate and 24% said it was easy. the level of web accessibility through e-learning media and video converence is often hampered by frequent web errors and also in terms of unstable internet signals. While the level of understanding of the material 12% of respondents said they had enough understanding, 5% understood 45% were difficult and 38% of other respondents said it was very difficult. The main inhibiting factor is in terms of the signal and the less optimal absorption of the material because more tasks are given than the explanation of the material